2005
DOI: 10.1021/nl051044e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductance and Thermopower of an Individual Single-Wall Carbon Nanotube

Abstract: We have observed experimentally that the thermal conductance of a 2.76-microm-long individual suspended single-wall carbon nanotube (SWCNT) was very close to the calculated ballistic thermal conductance of a 1-nm-diameter SWCNT without showing signatures of phonon-phonon Umklapp scattering for temperatures between 110 and 300 K. Although the observed thermopower of the SWCNT can be attributed to a linear diffusion contribution and a constant phonon drag effect, there could be an additional contact effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
600
5
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 824 publications
(643 citation statements)
references
References 26 publications
35
600
5
3
Order By: Relevance
“…We should note that the ratio isotope ðTÞ= pure ðTÞ for SWNTs is no longer expected to match our harmonic calculation for L larger than a few m above room temperature, since anharmonic scattering becomes important [29,30]. The predicted isotope effect reduction of the BN SWNTs thermal conductance is very strong, comparable to those experimentally reported for MWNTs (%0:5).…”
Section: -2supporting
confidence: 55%
See 1 more Smart Citation
“…We should note that the ratio isotope ðTÞ= pure ðTÞ for SWNTs is no longer expected to match our harmonic calculation for L larger than a few m above room temperature, since anharmonic scattering becomes important [29,30]. The predicted isotope effect reduction of the BN SWNTs thermal conductance is very strong, comparable to those experimentally reported for MWNTs (%0:5).…”
Section: -2supporting
confidence: 55%
“…The effect of such high isotope concentrations on thermal conductance has been experimentally reported for natural-abundance BN multiwalled NTs (MWNTs) (19.9% of 10 B and 80.1% of 11 B) [2]. Since the contact resistance was found to be minimal in small diameter (%1 nm) single-walled NTs (SWNTs) [29], the ratio of measured thermal conductivity between isotope pure and impure SWNTs should be independent of this effect. Our results In the same figure we show in dashed lines that, if WI effects due to multiple scattering could be neglected, this ratio for a certain length would be similar to the accurate result for roughly 2 times longer lengths.…”
Section: -2mentioning
confidence: 94%
“…[1][2][3] Of particular interest are carbon nanotubes, which have been proposed both as prototypical nanoscale circuit elements and by, virtue of their extraordinary current carrying capacity, as potential materials for interconnects. Recent studies have shown that nanotubes are remarkable thermal conductors [4][5][6][7][8] even at elevated temperatures 9,10 and ballistic phonon transport has been demonstrated in micron-scale devices, [11][12][13] with a mean free path in agreement to theoretical calculations. 14 Nevertheless, for thermal management it is also of interest to determine the thermal resistance between nanotubes and different materials.…”
mentioning
confidence: 55%
“…Another similar scenario is nanowire or nanotube arrays used as thermal interface materials. [11][12][13][14][15][16][17] Although heat spreading from an isolated nanotube to a substrate is highly ballistic, [18][19][20] it is not clear whether the same effect exists for arrays of nanowires and nanotubes as used for real thermal interface materials.…”
Section: Introductionsmentioning
confidence: 99%